Patellofemoral contact forces and knee gait mechanics 3 months after ACL reconstruction are associated with cartilage degradation 24 months after surgery. Issue 1 (January 2023) - Williams, J.R.; Neal, K.; Alfayyadh, A.; Capin, J.J.; Khandha, A.; Manal, K.; Snyder-Mackler, L.; Buchanan, T.S.
Summary: Objective: Evaluate patellofemoral cartilage health, as assessed by quantitative magnetic resonance imaging (qMRI) T2 relaxation times, 24-months after ACL reconstruction (ACLR) and determine if they were associated with patellofemoral contact forces and knee mechanics during gait 3 months after surgery. Design: Thirty individuals completed motion analysis during overground walking at a self-selected speed 3 months after ACLR. An EMG-driven neuromusculoskeletal model was used to determine muscle forces, which were then used in a previously described model to estimate patellofemoral contact forces. Biomechanical variables of interest included peak patellofemoral contact force, peak knee flexion angle and moment, and walking speed. These same participants underwent a sagittal bilateral T2 mapping qMRI scan 24-months after surgery. T2 relaxation times were estimated for both patellar and trochlear cartilage. Paired t -tests were used to compare T2 relaxation times between limbs while Pearson correlations and linear regressions were utilized to assess the association between the biomechanical variables of interest and T2 relaxation times. Results: Prolonged involved limb trochlear T2 relaxation times (vs uninvolved) were present 24-months after surgery, indicating worse cartilage health. No differences were detected in patellar cartilage. Significant negative associations were present within the involved limb for all the biomechanical variables of interest 3 months after ACLR and trochlear T2 relaxation times at 24-months. No associations were found in patellar cartilage or within the uninvolved limb. Conclusions: Altered involved limb trochlear cartilage health is present 24-months after ACLR and may be related to patellofemoral loading and other walking gait mechanics 3 months after surgery.